Analysis of Heavy Metal Content in Odaiba Waters, Japan Using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) - Hasya Ainun Nashih; Takato Negishi; Kuo Hong Wong; Asami Mashio; Hiroshi Hasegawa; Ali Ridlo; Sri Sedjati (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro, 2026)
This study aims to determine the content of dissolved heavy metals (Mn, Co, Ni, Cu, Zn, Cd, Pb) using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). This method was chosen because it has high sensitivity and the ability to detect elements in ultra-low concentrations accurately. Water samples were collected on July 13, 2024, and analyzed using selective resin and UV irradiation for the separation of metals. The results showed that primary metals (Zn, Mn, Ni, Cu) exceeded the CASS-6 reference limits, with Zn having the highest concentration (88.69 ± 1.92 nM). In contrast, minor metals (Cd, Pb, Co) were below the reference values, reflecting a stable distribution of heavy metals. The increase in significant metal concentrations is thought to be related to the timing of sampling in the summer, which coincides with the rainy season, potentially increasing runoff carrying heavy metals from the city center and industry to the waters of Odaiba. The detection results of minor metals in this study indicate that ICP-MS is effective for measuring heavy metal content at very low quantities. Environmental parameters, such as pH, temperature, and salinity, are also believed to influence the solubility and mobility of metals.